Pengaruh Tinggi Puncak Struktur Hexagonal Artificial Reef Terhadap Kemampuan Redamanan Gelombang - Muhammad Baharudin Fahmi; Haryo Dwito Armono; Muhammad Zikra; Harish Wirayuhanto (Universitas Trunojoyo Madura, 2022)
Generally, the purpose of artificial reefs is to rebuild naturally occurring coral reefs that have been destroyed. Without sacrificing the attractiveness of the protected beach, these manmade reefs functioned as new habitats for marine life and protected coasts by reducing wave energy. on the other side man-made artificial reefs can perform as submerged breakwaters, their ability to dampen incoming waves must be investigated. In this paper, the researchers present a new shape in the form of a hexagonal artificial reef. The wave attenuation performance index is calculated using the wave attenuation performance rating. The research focuses on the effect of structural height (h/d) on transmission wave value using a physical testing method on a scale of 1:10 at the wave flume of the Department of Marine Engineering, Sepuluh Nopember Institute of Technology, Surabaya. The test results indicate that the smallest transmission coefficient (KT) was produced on artificial reefs Configuration A-3 with the greatest submerged depth (h/d=0.75). The parameter results indicate that the greater the wave steepness (H/gT2) and the significantly larger the immersion depth (h/d), the better the wave reduction.